Arabidopsis NMD3 Is Required for Nuclear Export of 60S Ribosomal Subunits and Affects Secondary Cell Wall Thickening - Chen, Mei-Qin; Zhang, Ai-Hong; Zhang, Quan; Zhang, Bao-Cai; Nan, Jie; Li, Xia; Liu, Na; Qu, Hong; Lu, Cong-Ming; Sudmorgen; Zhou, Yi-Hua; Xu, Zhi-Hong; et al. (PLOS ONE, 2012)
NMD3 is required for nuclear export of the 60S ribosomal subunit in yeast and vertebrate cells, but no corresponding function of NMD3 has been reported in plants. Here we report that Arabidopsis thaliana NMD3 (AtNMD3) showed a similar function in the nuclear export of the 60S ribosomal subunit. Interference with AtNMD3 function by overexpressing a truncated dominant negative form of the protein lacking the nuclear export signal sequence caused retainment of the 60S ribosomal subunits in the nuclei. More interestingly, the transgenic Arabidopsis with dominant negative interference of AtNMD3 function showed a striking failure of secondary cell wall thickening, consistent with the altered expression of related genes and composition of cell wall components. Observation of a significant decrease of rough endoplasmic reticulum (RER) in the differentiating interfascicular fiber cells of the transgenic plant stems suggested a link between the defective nuclear export of 60S ribosomal subunits and the abnormal formation of the secondary cell wall. These findings not only clarified the evolutionary conservation of NMD3 functions in the nuclear export of 60S ribosomal subunits in yeast, animals and plants, but also revealed a new facet of the regulatory mechanism underlying secondary cell wall thickening in Arabidopsis. This new facet is that the nuclear export of 60S ribosomal subunits and the formation of RER may play regulatory roles in coordinating protein synthesis in cytoplasm and transcription in nuclei.